Web-Based Face Recognition using Line Edge Detection and Euclidean Distance Method - M. Iman Wahyudi; Eko Wahyu Wibowo; Sopiullah Sopiullah (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
A face recognition system is to perform a match face image using the face extraction method. There are many applications used in various algorithms and implemented in many programming languages, but still difficult to implement on web-based applications using the PHP programming language. The purpose of this research is to produce a website-based application focused on the face recognition section. The author will limit the system only to detect the front view of the face, the main goal is to get a fairly high level of accuracy. There will be a feature to find where the face is located. The research method used is a laboratory experiment where the search system scheme based on face recognition will produce the appearance of several faces that have the closest Euclidean distance values from grades 1st to 5th. The results from the comparison of the test image with the training image based on Line Edge Detection and Euclidean Distance calculation concluded that the system can be implemented in searching of similarity and recognizing the face.